2004
DOI: 10.1104/pp.103.036236
|View full text |Cite
|
Sign up to set email alerts
|

Light Induces Phosphorylation of Glucan Water Dikinase, Which Precedes Starch Degradation in Turions of the Duckweed Spirodela polyrhiza    

Abstract: Degradation of storage starch in turions, survival organs of Spirodela polyrhiza, is induced by light. Starch granules isolated from irradiated (24 h red light) or dark-stored turions were used as an in vitro test system to study initial events of starch degradation. The starch-associated pool of glucan water dikinase (GWD) was investigated by two-dimensional gel electrophoresis and by western blotting using antibodies raised against GWD. Application of this technique allowed us to detect spots of GWD, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 31 publications
1
36
0
1
Order By: Relevance
“…It has recently been reported that the in vitro degradation of granules isolated from turions of the duckweed by starch associated proteins (including a putative GWD ortholog) could be increased by addition of ATP, thereby enabling starch phosphorylation (Reimann et al, 2004). We have obtained similar results using potato leaf starch.…”
Section: Discussionsupporting
confidence: 73%
“…It has recently been reported that the in vitro degradation of granules isolated from turions of the duckweed by starch associated proteins (including a putative GWD ortholog) could be increased by addition of ATP, thereby enabling starch phosphorylation (Reimann et al, 2004). We have obtained similar results using potato leaf starch.…”
Section: Discussionsupporting
confidence: 73%
“…For some proteins, partitioning between the starch granule and the stroma has been reported to respond dynamically to the diurnal cycle of photosynthesis and carbon fl ow. Important examples include the diurnal change in partitioning of GWD (Ritte et al 2002;Mikkelsen et al 2005), α-amylase (Reimann et al 2004) and the dual specifi city phosphatatse SEX4 (Sokolov et al 2006). As several of these enzymes contain SBDs the question arises whether these modules contribute to the dynamic partitioning and what would be the functional requirement of this type of SBD.…”
Section: The Presence Of Carbohydrate-binding Modules In Intracellulamentioning
confidence: 99%
“…B-type crystalline polymorphs are typically more resistant towards amylolytic hydrolysis in vitro (Wickramasinghea et al 2009;Planchot et al 1997) forming a rational explanation for the phosphorylationdependent amorphisation of only this type of starch. In turions GWD is potentially autophosphorylated, or at least subject to major conformational changes, prior to starch phosphorylation (Reimann et al 2004). In potato (Solanum tuberosum) and pea (Pisum sativum) leaf cells, GWD is found bound to starch granule at night where starch degradation takes place (Ritte et al 2000a, b).…”
Section: Effects On Starch Degradationmentioning
confidence: 99%